Legal framework of private afforestation: The case of Turkey - Gencay, Gokce; Gençay, Gökçe (Elsevier Sci Ltd, 2020)
In Turkey, 99.9 % of the forest land belongs to the state, and according to the Turkish Constitution, the ownership of the state forests cannot be transferred to private parties or other non-state organizations. However, some permits have been granted to use and benefit from the state forests without transferring the ownership. One such is the private afforestation permit. Private afforestation aims to increase forest lands and the growing stock, to re-establish the deteriorating balance between soil, water, and plants, to improve the environmental value, and to provide income to natural entities. This study aims to identify the legal and administrative regulation dimensions of the land use policy on private afforestation in Turkey and to compare them with other successful international afforestation policies. The second part of this paper is a case study on the impact of the legal changes over time in private afforestation in the sample area. Interviews were conducted with participants in the program using questions addressing the socio-economic and cultural benefits of private afforestation along with their afforestation practices and problems. The overall conclusion of this survey was that private afforestation practice had contributed to the income level of the participants. Further, to increase the participation in the program, more public awareness was necessary and incentives to participate must be increased.
Keywords: Private Afforestation; Income-Generating Species; Forest Law; Turkey